AUTO DOCUMENTATION TO HOSPITAL INFORMATION SYSTEM USING BAR-CODED MEDICATION ADMINISTRATIONâ€ - Jain, Mohit; Rani, Shola Usha (Asian Journal of Pharmaceutical and Clinical Research, 2017)
This paper is mainly on patient safety in health-care information technology (HIT). One of the main concerns with respect to this is recording all patient related information. One of the issues is auto documentation in HIT. Due to this, many medical errors are occurring, to avoid this automation to the patient history need to be supported. The patient will be linked with history, prescription, doctors, and nurse's information. All this information should be linked with one patient ID known as bar code. The outcome of care transformations of the medication administration process that resulted from the implementation of one type of IT: Bar-coded medication administration (BCMA). Hence, this paper shows the technologies of BCMA how it works and the drawback of it and the implementation on open-source platform of BCMA.